The Development of Water Filtering with Digital Monitoring System Together with Cloud System and Hot-Cold Process Using Thermoelectric Module System II: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the common health issues people experience worldwide is unexpectedly drinking contaminated water that threatens people's health, like dehydration and diarrhea. The researchers conducted this research to spread public awareness regarding the possible cause of unsafe water. We develop smart water quality monitoring using IOT technology so that the user can monitor the water quality without human intervention.Quantitative research was used as a research design for the study. Using the instrument of the study, a survey questionnaire, the researchers surveyed to determine the respondents' perceptions of the existing water filter process in terms of their reliability.The result of this study in terms of reliability, efficiency, and security of developing a water filtering process together with a cloud system and hot and cold water using thermoelectric module system II was for the safety of the respondents/ users to produce clean, safe drinking water.This research aimed to remove particulate and other matter concentrations, including suspended particles, parasites, and bacteria, and remove water contaminants to produce safe and clean water for better, healthy, and safe drinking water. This research also presented water quality monitoring using IOT technology. The system can be monitored from a PC using a Thingspeak platform, and it is low in cost and does not require people on duty. It provides quick and easy monitoring of pH value and tank storage to maintain clean water continuously. With fast feedback, the researchers` technology makes water quality monitoring more convenient and reliable. The researchers can guarantee a safe method of drinking water using water filtration such as sediment filter, carbon filter, NF membrane, and UV sterilizer light. Besides water filtration, users are guaranteed the safety of the water using electronic components such as pH sensors and DS18B20 with the help of Arduino, an open-source electronics platform based on easy-to-use hardware and software. Using the electronic components can guarantee the safety of the water by monitoring the pH value "water quality". The combination of water filtration and electronics components can ensure the water you consume has a better taste and smell, removes bad bacteria, and provides necessary vitamins and minerals.
Keywords: IOT technology; human intervention; Thingspeak platform; Filter process